2010
DOI: 10.1016/j.envres.2010.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Redox and electrophilic properties of vapor- and particle-phase components of ambient aerosols

Abstract: Particulate matter (PM) has been the primary focus of studies aiming to understand the relationship between the chemical properties of ambient aerosols and adverse health effects. Size and chemical composition of PM have been linked to their oxidative capacity which has been postulated to promote or exacerbate pulmonary and cardiovascular diseases. But in the last few years, new studies have suggested that volatile and semivolatile components may also contribute to many adverse health effects. The objectives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…In this regard, we have previously demonstrated that there is an excellent correlation between the PAH content of ambient UFP and their ability to act as an adjuvant in the primary immune response (36). Quinones, which can also be formed from the enzymatic conversion of PAH, are capable of generating ROS through redox cycling and electrophilic chemistry that may be relevant to the generation of oxidative stress deep in the lungs of the animals (15,37,57). The particle exposure site in this study is generally characterized by a higher content of redoxcycling organic chemicals as also evidenced by the high OC content (81.6%) of the particles that were collected near the 110 Los Angeles Freeway (Supplemental Fig.…”
Section: L379mentioning
confidence: 99%
“…In this regard, we have previously demonstrated that there is an excellent correlation between the PAH content of ambient UFP and their ability to act as an adjuvant in the primary immune response (36). Quinones, which can also be formed from the enzymatic conversion of PAH, are capable of generating ROS through redox cycling and electrophilic chemistry that may be relevant to the generation of oxidative stress deep in the lungs of the animals (15,37,57). The particle exposure site in this study is generally characterized by a higher content of redoxcycling organic chemicals as also evidenced by the high OC content (81.6%) of the particles that were collected near the 110 Los Angeles Freeway (Supplemental Fig.…”
Section: L379mentioning
confidence: 99%
“…A variety of quinones, including 1,4-benzoquinone (1,4-BQ), 1,2-naphthoquinone (1,2-NQ), and 1,4-NQ are found in diesel engine exhaust, burning coal, cigarette smoke (Eiguren-Fernandez et al, 2010;Batterman et al, 2012;Wallace, 1989) and as metabolites during exposure of experimental animals and cultured cells (Wilson et al, 1996). Butylated hydroxyanisol (BHA) and tert-butyl-1, 4-hydroquinone (TBHQ), which are used as a food and cosmetic additive to preserve oils, are metabolized to tertbutyl-1,4-benzoquinone (TBQ) (Verhagen et al, 1989;Snyder and Hedli, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring atmospheric aerosol is important for several reasons: the toxic nature of the particles due to the organic compounds on itself (Eiguren-Fernandez et al, 2010), the ability of UFPs to penetrate in the epithelial cells of the lower respiratory tract and accumulate in lymph nodes (Nel et al, 2006), the oxidative damage effects on DNA which may increase the risk of cancer (Møller et al, 2008), and the potential association with paediatric asthma (Andersen et al, 2008) are some of the harmful effects on human health caused by exposure to nanoparticles.…”
Section: Ultrafine Particles In Urban Areasmentioning
confidence: 99%